Successful use of email in a week - Langford-Wood, Naomi (Hodder & Stoughton, 1999)
However large or small an individuals role in an organisation, e-mail can dynamise the way one works. This book has been written as a practical guide to this on-demand, 24-hour communications medium, demonstrating how to increase efficiency, communicate more effectively, reduce costs, and improve turn-around times and customer service levels.